Socioeconomic status, psychotherapy duration, and return to work from disability due to common mental disorders - Leppänen Helena; Kampman Olli; Autio Reija; Karolaakso Tino; Rissanen Päivi; Nappila Turkka; Pirkola Sami (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Objective: Low socioeconomic status (SES) is a risk factor for work disability due to common mental disorders (CMDs), one possible reason being inequal use of services. Psychotherapy is an evidence-based treatment for CMDs. This study examines socioeconomic and sociodemographic differences in psychotherapy attendance and an association of psychotherapy duration with return to work (RTW).
Methods: The study subjects (N = 12,263) were all Finnish citizens granted a disability pension (DP) due to CMDs in 2010-2012. Numbers of psychotherapy sessions (maximum 200) were collected from the nine-year interval around the DP grant. Socioeconomic and sociodemographic differences in psychotherapy duration (dependent variable) among DP recipients were studied using multinomial logistic regression models, likewise, the association between psychotherapy duration and RTW (dependent variable) among temporary DP recipients was examined.
Results: Higher SES, female gender, and younger age were positively associated with attending longer psychotherapies and surpassing the early treatment termination level (>10 sessions). Attending 11-60 psychotherapy sessions was positively associated with full RTW and partial RTW, whereas longer psychotherapies were not. Early termination was positively associated with partial RTW only.
Conclusion: This study demonstrates varying tendencies among CMD patients from different backgrounds to attend long rehabilitative psychotherapies, which may create inequalities in RTW.